Social Determinants of Health: A Multilingual Standardized Patient Case to Practice Interpreter Use in a Telehealth Visit - Gigi Guizado de Nathan; Laura K. Shaw; Jessica Doolen (Association of American Medical Colleges, 2023)
Introduction The growing diversity of the United States population and strong evidence of disparities in health care make it critically important to educate health care professionals to effectively address issues of culture. To that end, we developed a simulation for teaching interpreter use in a telehealth setting. Our contribution of non-English language preference (NELP) patient cases in Spanish, Tagalog, French, and Igbo advances existing literature by combining the skills of interpreter use and telehealth while widening the array of cultures represented. Methods Simulations were implemented for two cohorts of 60 first-year medical students. In the pilot, nine groups of six to seven students and one faculty met via Zoom with an NELP patient complaining of fatigue, weakness, and cough. When students determined the need for an interpreter, faculty admitted one to the meeting, and the telehealth visit continued. Postsession activities included debriefing and writing a progress note. Results Course evaluation comments from the first cohort and a postencounter survey of the second cohort were positive. They revealed that students learned to speak slower, in shorter phrases, and directly to the patient. Learners completed note documentation according to a rubric. Discussion This low-stakes activity provides faculty with a resource for introducing cultural competence into the curriculum. The original Spanish version of the case has been translated into three additional languages, providing a diverse representation of the NELP population. Important points for communicating through an interpreter are practiced in a telehealth setting with a fatigue case.